Gramineous Plants as Phytoremediation Candidates for Metal Contaminated Mining Soils under Drought Stress - Honglei Jia; Zhiwei Ran; Qing Wang; Haodong An; Ting Wei; Chunping Zhang; Gang Zhu; Junkang Guo (Water, Air, & Soil Pollution, 2026)

A Hybrid KF-RDT-SSI Framework for Operational Modal Analysis of Offshore Jacket Platforms: Full-Scale Field Evaluation - Peng Zhang; Xiaokang Liu; Ziguang Jia; Zhengjie He; Ran An; Qingmin Hou (Journal of Marine Science and Engineering, 2026)
Operational modal analysis (OMA) is important for continuous structural health monitoring (SHM) of in-service offshore jacket platforms. In practice, long monitoring records increase the computational cost of SSI, while environmental and measurement interference can affect the recorded response. This study applies a hybrid procedure combining Kalman filtering (KF), the Random Decrement Technique (RDT), and Stochastic Subspace Identification (SSI). KF is used as a fixed-parameter preprocessing step, RDT extracts shorter free-decay signatures, and SSI is used to identify the natural frequency. The procedure is examined using a finite element (FE) model, a laboratory-scale model, and full-scale measurements from the same operating offshore platform represented by the FE model. For a representative 50 Hz record, RDT reduced the data entering SSI from 38,553 to 1200 samples (96.89%) and reduced the number of Hankel-matrix elements by 97.05%. Under identical SSI settings, the complete KF-RDT-SSI procedure required about one-fifth of the Standard SSI runtime in the benchmark environment. In the four-channel laboratory test, the dominant spectral peak remained at 6.1279 Hz before and after KF processing. KF-RDT-SSI identified 6.1204–6.1353 Hz, with a mean absolute relative deviation of 0.095% from the FFT result. The field measurements identified the fundamental natural frequency at approximately 1.56–1.57 Hz under transient and continuous operating conditions. The full-scale measurements provide the main evidence for the field applicability of the procedure. A systematic assessment under controlled noise types and signal-to-noise ratios is left for future work.

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

C10–C12 aromatics dominate ozone and secondary organic aerosol formation potential in emissions from printed circuit board manufacturing - Xiaodie Pang; Wei Song; Weiqiang Yang; Chao Peng; Jianqiang Zeng; Zhou Zhang; Xiao Tian; Hongcheng Lu; Xiangyu Zhang; Ran An; Yang Li; Runcheng Zhu; et al. (Journal of Environmental Sciences, 2026)

Assessment of applicators’ exposure to pesticides during knapsack mist sprayer application in rice fields - Mei Chenghan; Tao Chuanjiang; Zhang Liying; Meng Yuxi; Nie Siqiao; Pu Entang; An Xuehua; Qu Mengmeng; Tao Lingmei; Liu Ran; Huang Lan; Zhang Bingmei (Environmental Toxicology and Pharmacology, 2026)

Revealing uncertainties of on-road emissions in a mountainous city using multi-source data - Zeyu Zhang; Qiuzi Chen; Weizhen Lin; Ran Tu; Wenyu Wang; Xiaotong Zhang; An Wang (Transportation Research Part D: Transport and Environment, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Does corporate climate risk promote climate response actions? Empirical evidence from China - Ran Yi; Yunfan Zhang; An Chen (Mitigation and Adaptation Strategies for Global Change, 2026)

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

An efficient multi-objective optimization method for inter-basin water diversion based on the rotation vector method for exploring the convex objective space - Zekun Li; Bin Xu; Ping-an Zhong; Jiaying Tan; Ran Mo; Xinrong Wang; Zichen Ren; Guoqing Wang; Jianyun Zhang; Jiangyuan Li; Scott E. Boyce (Environmental Modelling & Software, 2026)

Characterizing low-supersaturation CCN activity with AAC-CCNC system at a mountain site in continental region in China - Mengyao An; Jiangchuan Tao; Yaqing Zhou; Minghua Liang; Li Li; Juan Hong; Linhong Xie; Weikang Ran; Shaobin Zhang; Qiaoqiao Wang; Qiyuan Wang; Nan Ma (Atmospheric Research, 2026)

Rhein Prevents APAP-induced drug-induced Liver Injury by Upregulating Nrf2 and Inhibiting APAP-activating Enzymes - Mingda Liu; Jin Dai; Liangding Dou; Zifeng Deng; Junxian Liu; Xin Hou; Jinwen Zhang; YongChao Huang; Zhi Huang; Dai Wang; Dongbei Guo; Ran An; et al. (Cell Biochemistry and Biophysics, 2026)

Spatiotemporal correction of decision variables using XGBoost for multi-objective intelligent scheduling rule extraction model in reservoir-lake flood control systems - Huili Wang; Bin Xu; Xinman Qin; Xinrong Wang; Jianyun Zhang; Guoqing Wang; Fubao Yang; Ping-an Zhong; Ran Mo; Xuesong Yang (Environmental Modelling & Software, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

A core-damage zone architecture of the ultra-deep carbonate strike-slip fault zones: a case study from the Shunbei area in Tarim Basin, China - Yuan Kang; Xinjing Yu; Min Xiang; Ran An; Fanfan Yang; Fengwei Zhang (Carbonates and Evaporites, 2025)

Excessive health risks of summer aerosol sources related to particle-bound toxic metals in the Tibetan Plateau, China - Jiwei Li; Yunfei Wu; Zhaoze Deng; Liang Ran; Yunjie Xia; Jianchun Bian; Renjian Zhang; Yang Yu; Jiutao An (Environmental Pollution, 2025)

Unexpected benefits of agricultural greenhouses in mitigating ozone pollution on crop yields in China - Jingwei Zhang; Yuanqi Huang; Xiaoye Tong; Hailin Wu; Haiyan Ran; Wenxuan Fan; Yuanzhe Li; Shijing Dong; Shengsen Zhou; Jiangping Liu; Dawei Lu; Huizhi Liu; et al. (Atmospheric Environment, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Evaluating parameterization schemes of dinitrogen pentoxide heterogeneous processes in the presence of organic coatings for size-resolved nitrate simulations over North China - Yu Qu; Juan Yang; Yitian Guo; Yong Chen; Xingang Liu; Hui Chen; Haiyan Ran; Jingwei Zhang; Ying Li; Junling An (Atmospheric Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Bioremediation strategies for hexavalent chromium: Development and safety assessment of recombinant Escherichia coli strain 3458 - Yeting Weng; Qiuying An; Dongbei Guo; Ningjing Gan; Weijie Zeng; Wanting You; Zhangye Ma; Jiayan Qi; Zhiyu Zhang; Lirong Zhang; Mufeng Liang; Hongyuan Zeng; et al. (Journal of Environmental Management, 2025)

Effect of lipoxygenase-catalyzed oxidation of linoleic acid on the molecular structure and gelation properties (e.g., strength, water-holding capacity) of wheat germ protein - Ling Xiong; Chunyan An; Hongfei Zhang; Ran Chen; Luanfeng Wang; Haizhao Song; Fang Wang; Xinchun Shen (Journal of Cereal Science, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Emission characteristics of indoor HONO from residential natural gas cooking stoves in a household in Kunming, China - Hailin Wu; Haiyan Ran; Shijing Dong; Lingling Li; Jiangping Liu; Wenxuan Fan; Dawei Lu; Jingwei Zhang; Junling An (Journal of Hazardous Materials, 2025)

HONO chemistry affected by relative humidity and ammonia in the North China Plain during winter - Haiyan Ran; Jingwei Zhang; Yu Qu; Juan Yang; Yong Chen; Yele Sun; Chaoyang Xue; Yujing Mu; Junling An (Atmospheric Environment, 2025)

Follicle mural granulosa cells encapsulated in sodium alginate gel improve developmental competence of porcine oocytes of in vitro maturation - Qi Zhang; Yongfeng Zhou; Ran Ding; Qi Li; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Decoding microstructural evolution and mechanical degradation of micaceous granite residual soils as marginal geomaterials in tropical climates - Haodong Gao; Xianwei Zhang; Ran An; Gang Wang; Xinyu Liu; Huicheng Fu (Engineering Geology, 2025)

Responses of intestinal microbiota to inulin was initial microbiota context dependent and affected by the supplementation dosage - Ran An; Xilong Zhou; Jing Zhang; Chenang Lyu; Dapeng Wang (Food Research International, 2025)

Quantification and division of unfrozen water content of frozen soils during freezing and the influence of freeze-thaw cycles - Ran An; Haodong Gao; Chang Chen; Xianwei Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Reactive species of plasma-activated water for murine norovirus 1 inactivation - Fengqing Wang; Qing Zhang; Ran An; Chenang Lyu; Jialun Xu; Dapeng Wang (Food Research International, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Impact of soil–atmosphere HONO exchange on concentrations of HONO and O3 in the North China Plain - Haiyan Ran; Junling An; Jingwei Zhang; Junjie Huang; Yu Qu; Yong Chen; Chaoyang Xue; Yujing Mu; Xingang Liu (Science of The Total Environment, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Compaction, compression, and hydraulic characteristics of micaceous residual soil - Haodong Gao; Xianwei Zhang; Ran An; Gang Wang; Xinyu Liu; Xuewen Lei (Bulletin of Engineering Geology and the Environment, 2024)

Unraveling the two-sided effect of nitrate on aerobic granulation - Xiaochuan Ran; Xinyi Zhang; Bin Zhao; Qiang An (Chemical Engineering Journal, 2024)

Engineering geological characterization of micaceous residual soils considering effects of mica content and particle breakage - Gang Wang; Xianwei Zhang; Xinyu Liu; Haodong Gao; Ran An; Lei Yan (Engineering Geology, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Experimental assessment of clayey layers for clogging potential in TBM tunnel driving and the influence of compositional factors - Gang Wang; Xianwei Zhang; Xinyu Liu; Haodong Gao; Ran An; Song Yin (Tunnelling and Underground Space Technology, 2023)

Long-term probabilistic streamflow forecast model with “inputs–structure–parameters” hierarchical optimization framework - Ran Mo; Bin Xu; Ping-an Zhong; Yuanheng Dong; Han Wang; Hao Yue; Jian Zhu; Huili Wang; Guoqing Wang; Jianyun Zhang (Journal of Hydrology, 2023)

MDNet: A Fusion Generative Adversarial Network for Underwater Image Enhancement - Song Zhang; Shili Zhao; Dong An; Daoliang Li; Ran Zhao (Journal of Marine Science and Engineering, 2023)
Underwater images are widely used in ocean resource exploration and ocean environment surveillance. However, due to the influence of light attenuation and noise, underwater images usually display degradation phenomena such as blurring and color deviation; an enhancement method is required to make the images more visible. Currently, there are two major approaches for image enhancement: the traditional methods based on physical or non-physical models, and the deep learning method. Inspired by the fusion-based idea, this paper attempts to combine traditional methods with deep learning and proposes a multi-input dense connection generator network (MDNet) for underwater image enhancement. Raw images and processed images are input into the network together, the shallow information is fully utilized by dense connection, and the network is trained in generative and adversarial manner. We also design a multiple loss function to improve the visual quality of the generated images. We conduct both qualitative and quantitative experiments, and then compare the results with state-of-the-art approaches comprehensively using three representative datasets. Results show that the proposed method can effectively improve the perceptual and statistical quality of underwater images.

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Research on quantitative method of fish feeding activity with semi-supervised based on appearance-motion representation - Yaqian Wang; Xiaoning Yu; Jincun Liu; Ran Zhao; Liu Zhang; Dong An; Yaoguang Wei (Biosystems Engineering, 2023)

Quantitative characterization of drying-induced cracks and permeability of granite residual soil using micron-sized X-ray computed tomography - Ran An; Yixian Wang; Xianwei Zhang; Chang Chen; Xinyu Liu; Sutong Cai (Science of The Total Environment, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Xenogenetic evolutionary of integrons promotes the environmental pollution of antibiotic resistance genes — Challenges, progress and prospects - Ran An; Yuting Qi; Xu-Xiang Zhang; Liping Ma (Water Research, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Drying-wetting impacts on granite residual soil: a multi-scale study from macroscopic to microscopic investigations - Ran An; Xianwei Zhang; Lingwei Kong; Xinyu Liu; Chang Chen (Bulletin of Engineering Geology and the Environment, 2022)

Influent salinity affects substrate selection in surface flow constructed wetlands - Shenyan Zhou; Ran Zhao; Qiming Li; Juan Du; Chen Chen; Qianqian Lu; Miao Zhang; Dehua Zhao; Shuqing An (Environmental Science and Pollution Research, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

Temporal variation of airborne fungi in university library rooms and its relation to environmental parameters and potential confounders - Dingmeng Wu; Ying Zhang; Chenbo Zhao; Angui Li; Li’an Hou; Yu Tian; Jing Xiong; Ran Gao (Environmental Science and Pollution Research, 2021)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Hypothesized mechanism of biocontrol against pine wilt disease by the nematophagous fungus Esteya vermicola - Can Yin; Yunbo Wang; Yong-an Zhang; Haihua Wang; Beibei Duan; Ran Tao; Jie Gao; Chang-keun Sung (European Journal of Plant Pathology, 2020)

A combination of Citrus reticulata peel and black tea inhibits migration and invasion of liver cancer via PI3K/AKT and MMPs signaling pathway - Shuai Wen; Lingli Sun; Ran An; Wenji Zhang; Limin Xiang; Qiuhua Li; Xingfei Lai; Mengen Huo; Dongli Li; Shili Sun (Molecular Biology Reports, 2020)

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

Identification of Resveratrol, an Herbal Compound, as an Activator of the Calcium-Activated Chloride Channel, TMEM16A - Ran Chai; Yafei Chen; Hongbo Yuan; Xuzhao Wang; Shuai Guo; Jinlong Qi; Hailin Zhang; Yong Zhan; Hailong An (The Journal of Membrane Biology, 2017)

Integrated RNA-seq and sRNA-seq analysis reveals miRNA effects on secondary metabolism in Solanum tuberosum L - Yan Qiao; Jinjin Zhang; Jinwen Zhang; Zhiwei Wang; An Ran; Haixia Guo; Di Wang; Junlian Zhang (Molecular Genetics and Genomics, 2017)

Two Ca2+-Binding Sites Cooperatively Couple Together in TMEM16A Channel - Yuebin Han; Suhua Zhang; Shuxi Ren; Yafei Chen; Hongbo Yuan; Ran Chai; Hui Yu; Hailin Zhang; Yong Zhan; Hailong An (The Journal of Membrane Biology, 2016)

Effect of polyelectrolyte adsorption on lateral distribution and dynamics of anionic lipids: a Monte Carlo study of a coarse-grain model - Xiaozheng Duan; Ran Zhang; Yunqi Li; Yongbiao Yang; Tongfei Shi; Lijia An; Qingrong Huang (European Biophysics Journal, 2014)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)